Message From The Chief Editor - Editor, Chief (Journal of Technical Education and Training, 2014)
Welcome to the first issue for the year 2014 of the Journal of Technical Education and Training (JTET). In this issue, we have seven interesting articles on teaching and learning and management of TVET. Readiness level seems to be the underpinning theme - among TVET teachers and students - in this issue. In the first paper, Audu et al reports on the low readiness level of Kenyan TVET teachers to undertake their professional role. Lack of pedagogical and practical skills was found to be a cause for concern in general. Their article suggests future initiatives to improve the situations that can be useful to other agencies experiencing similar situations. In addition to teachers’ readiness, students’ readiness is also critical in efforts to achieve the expected learning outcomes. Placing equal emphasis on the affective and cognitive (dual) learning needs is one approach for ensuring students’ readiness for learning as reported in the second article by Lashari and Alias. This article specifically reports on the effect of an integrated approach that meets the dual learning needs of engineering students. A framework used to develop the learning materials was also discussed in detail which can be useful to TVET teachers for materials preparations in engineering related disciplines. Increasing students’ readiness through learning materials that are more aligned with their learning preferences is also a way to increase students’ readiness. In the third article, Mohamad, Yee and Tee contemplate on the different learning style models and how they can be integrated into a useful model for applications in TVET teaching and learning practices. A factor that may contribute to students’ readiness for learning is the conduciveness of the learning environment itself. To assess the level of conduciveness, a valid and reliable measuring tool must be in place. In the fourth paper, Yusof et al. discusses the efforts made to evaluate and validate an existing tool for assessing learning environment in TVET. The discussion of the validation process can bring a better understanding on instrument development and validation in general which is an added benefit to the validated instrument. Both students’ and teachers’ readiness is especially critical where new innovations are introduced. With increasing use of ICT innovations in teaching and learning practices, and in management of TVET, more efforts are being made to understand factors that may contribute to the success of such initiatives. In the fifth article, by Ruhizan et al., they discuss one potential factor that is, the readiness in using e-portfolios among vocational teacher and students in relation to its successful implementation in vocational education. They provide findings and recommendations that can be useful to managers and practitioners who are at the early stage or planning to implement e-portfolios. Outside the national TVET system, vocational trainings are often adopted as the solution in promoting successful career move in certain professions such as the military service. In career change, where the repercussion of failure is enormous, readiness becomes more crucial. In the sixth paper, Zakaria et al. investigate the readiness of military retirees for career change as indicated by their competence in managing their vocational skills development. Interesting findings related to retirees’ readiness and readiness of training providers are discussed for greater understandings. Going international, Maringa’s article discusses the initiatives that can be implemented to improve the industry readiness TVET graduates in Kenya. The articles’ recommendations based on extensive situational analysis will be useful to TVET managers and practitioners worldwide. I hope that these articles are useful and have encouraged more thoughts on the relevance of readiness in ensuring learning in TVET. My heartiest gratitude goes to article contributors, reviewers and technical support personnel for making this issue possible. For future issues, I would like to invite practitioners, TVET researchers and graduate students to publish their research findings with us. The next time you publish with us, JTET may already be indexed by Scopus. Professor Dr. Maizam Alias